A new genus and six new species of Namaini from the Richtersveld (South Africa, Northern Cape) (Coleoptera: Curculionidae: Entiminae) - Borovec, Roman; Meregalli, Massimo (Zootaxa, 2026)
One new genus and six new species of Namaini are described: Richtersveldiella sanparkensis Borovec and Meregalli, new genus and new species (type locality: Koeroegab); Pentamerica gazella Borovec and Meregalli new species (type locality: Kodaspiek); Namaquania hirta Borovec and Meregalli new species (type locality: Armmanshoek valley); Nama mirifica Borovec and Meregalli new species (type locality: south of Helskloof Pass); Nama vanwyki Borovec and Meregalli new species (type locality: Armmanshoek valley); Nama armmanshoek Borovec and Meregalli new species (type locality: Armmanshoek valley). Biological notes and comparative remarks are added, along with considerations on their distribution. An assessment of their conservation status is also proposed.